Enlightenment of the Mariana Fore‐arc Sedimentary Basin Evolution to the Subduction Process. (24th February 2022) - XING, Lei; LI, Qianqian; MENG, Qingwei; LIU, Huaishan; WEI, Jia; LÜ, Boran; ZHOU, Heng
Abstract : Abstract: The Mariana subduction structure is a hot topic in ocean‐ocean subduction zone research, and its subduction mechanism has attracted wide attention from experts and scholars in China and abroad. Based on the multi‐channel seismic data of survey line MGL1204 in the Mariana fore‐arc and DSDP ocean drilling data, this paper studies the development and evolution characteristics of the structure and strata in the Cenozoic Mariana fore‐arc sedimentary basin. The Cenozoic strata are divided into six seismic sequences, with the possible era of each seismic sequence discerned, and the relationship between fault development and earthquakes analyzed. The episodic activity of the volcanic chain of the Mariana island arc is thought to control the tectonic and stratigraphic development pattern of the Cenozoic sedimentary basin in the fore‐arc. Between 16°N–19°N and 146°E–151°E, the maximum thickness of the sedimentary center of the Cenozoic fore‐arc sedimentary basin in Mariana is about 2360 m. Normal faults are developed in the area and some broke to the seabed, indicating that the Mariana island arc is still in the post‐arc expansion stage. The application of multi‐channel seismic sections in structural and stratigraphic evolution study is an important means to elucidating the Mariana subduction mechanism.